Occupational exposure to carcinogens in Estonia, Latvia, Lithuania and the Czech Republic in 1997 - Kauppinen, Timo; Pajarskiene, Birute; Podniece, Zinta; Rjazanov, Vladislav; Smerhovsky, Zdenek; Veidebaum, Toomas; Leino, Timo (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'The aim of the study was to estimate the numbers of workers exposed to carcinogens in Estonia, Latvia, Lithuania, and the Czech Republic. ' ' METHODS ': 'CAREX is an international information system on occupational exposure to 139 known and suspected carcinogens. It provides exposure data and estimates of the numbers of exposed workers by country, carcinogen, and industry. The CAREX method, which has been previously applied in the member states of the European Union, was applied in the present study to the exposure situation in Estonia, Latvia, Lithuania, and the Czech Republic in 1997. The preliminary estimates generated by CAREX were reviewed and revised by national experts mainly for asbestos, benzene, and lead, which were of special interest for this project. ' ' RESULTS ': 'The numbers of workers exposed to carcinogens covered by CAREX in 1997 were about 180 000 (29% of employed persons) in Estonia, 260 000 (28% of employed persons) in Latvia, 470 000 (28% of employed persons) in Lithuania, and 1 400 000 (28% of employed persons) in the Czech Republic. The most common exposures were solar radiation (7-13% exposed at least 75% of the worktime), environmental tobacco smoke (4-5% exposed at least 75% of the worktime), wood dust (3-5% exposed), crystalline silica (2-3% exposed), diesel exhaust (2-3% exposed), radon and its decay products (2% exposed), benzene (0.9-1.7% exposed), and lead and inorganic lead compounds (0.8-1.4% exposed). Exposure to asbestos was slightly less prevalent (0.3-1.1% exposed). ' ' CONCLUSIONS ': 'These preliminary results indicate that a substantial proportion of the workers in the studied countries were exposed to carcinogens.
Keywords: asbestos; benzene; carcinogen; carex; Czech Republic; diesel exhaust; environmental tobacco smoke; Estonia; Latvia; lead; Lithuania; occupational exposure; radon; short communication; silica; solar radiation; wood dust